5G Fixed Beam Switching on Microstrip Patch Antenna - Low Ching Yu; Muhammad Ramlee Kamarudin (Institute of Advanced Engineering and Science, 2017)
5G technology is using millimeter-wave band to improve the wireless communication system. However, narrow transmitter and receiver beams have caused the beam coverage area to be limited. Due to propagation limitations of mm wave band, beam forming technology with multi-beam based communication system, has been focused to overcome the problem. In this letter, a fixed beam switching method is introduced. By changing the switches, four different configurations of patch array antennas are designed to investigate their performances in terms of radiation patterns, beam forming angle, gain, half-power bandwidth and impedance bandwidth at 28 GHz operating frequency for 5G application. Mircostrip antenna is preferred due to its low profile, easy in feeding and array configurations. Three different beam directions had been formed at -15°, 0°, and 15° with half-power bandwidth of range 45˚ to 50˚.